Intravoxel Incoherent Motion Diffusion-Weighted Imaging Used to Detect Prostate Cancer and Stratify Tumor Grade: A Meta-Analysis - He, Ni; Li, Zhipeng; Li, Xie; Dai, Wei; Peng, Chuan; Wu, Yaopan; Huang, Haitao; Liang, Jianye (Frontiers in Oncology, 2020)
Objectives: Intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) is a promising noninvasive imaging technique to detect and grade prostate cancer (PCa). However, the results regarding the diagnostic performance of IVIM-DWI in the characterization and classification of PCa have been inconsistent among published studies. This meta-analysis was performed to summarize the diagnostic performance of IVIM-DWI in the differential diagnosis of PCa from noncancerous tissues and to stratify the tumor Gleason grades in PCa. Materials and Methods: Studies concerning the differential diagnosis of prostate lesions using IVIM-DWI were systemically searched in PubMed, Embase and Web of Science without time limitation. Review Manager 5.3 was used to calculate the standardized mean difference (SMD) and 95% confidence intervals of the apparent diffusion coefficient (ADC), tissue diffusivity (D), pseudodiffusivity (D*), and perfusion fraction (f). Stata 12.0 was used to pool the sensitivity, specificity, and area under the curve (AUC), as well as publication bias and heterogeneity. Fagan’s nomogram was used to predict the posttest probabilities. Results: Twenty studies with854 patients confirmed with PCa were included. Most of the included studies showed a low to unclear risk of bias and low concerns regarding applicability. PCa showed a significantly lower ADC (SMD=-2.34; P<0.001) and D values (SMD=-1.86; P<0.001), and a higher D* value (SMD=0.29; P=0.01) than noncancerous tissues, but no difference was noted with the f value (SMD=-0.16; P=0.50). Low-grade PCa showed higher ADC (SMD=0.63; P<0.001) and D values (SMD=0.80; P<0.001) than the high-grade lesions. ADC showed comparable diagnostic performance (sensitivity=86%; specificity=86%; AUC=0.87) but higher posttest probabilities (60%, 53%, 36% and 36% for ADC, D, D* and f values, respectively) compared with the D (sensitivity=82%; specificity=82%; AUC=0.85), D* (sensitivity=70%; specificity=70%; AUC=0.75) and f values (sensitivity=73%; specificity=68%; AUC=0.76). Conclusion: IVIM parameters are adequate to differentiate PCa from noncancerous tissues with good diagnostic performance but are not superior to the ADC value. Diffusion coefficients can further stratify the tumor Gleason grades in PCa.